HUBUNGAN POLA ASUH ORANG TUA DENGAN TINGKAT KEMANDIRIAN ACTIVITY OF DAILY LIVING PADA ANAK TUNAGRAHITA - Niswah , Resti Khoirotun; Maghfuroh, Lilis; Martini , Diah Eko (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective : Independence in activities of daily living (ADL) refers to the fundamental ability to perform daily tasks without dependence. A lack of independence in children with intellectual disabilities can lead to increased reliance on their environment and delays in skill development. Methods: This research employed a quantitative descriptive design with a cross-sectional approach. The study population comprised 45 parents of children with intellectual disabilities, with a final sample of 40 respondents selected using consecutive sampling. Data were collected through a parenting style questionnaire and the Katz Index of Independence in ADL questionnaire.and data were analyzed using the Contingency Coefficient Test.Results: The findings reveal that parents who adopted an authoritative parenting style tend to have children with a high level of independence (65.7%). In contrast, an authoritarian parenting style resulted in children with moderate dependency (100%), while a permissive parenting style led to severe dependency (100%). Conclusion: Based on these findings, implementing authoritative parenting strategies could enhance independence in ADL for children with intellectual disabilities, reducing their dependency on external assistance and promoting skill development.